Principles Methodology on Quranic Interpretation in Indonesia [Analysis on Interpretation Method of Tafsir Al-Azhar And Tafsir Al-Misbah] - Nuraini, Nabilah; Zulaiha, Eni (UIN Sunan Gunung Djati Bandung, 2022)
The interpretator's background influences the style and characteristics of the interpretation he writes. Likewise, the interpretation products in Indonesia will be very different from the interpretations from the Middle East. From this background, the researcher will reveal the uniqueness and characteristics of interpretation in Indonesia through the methodological principles used in its interpretation. The object of this research is Tafsir Al-Misbah by Quraish Shihab and Tafsir Al-Azhar by Hamka. From this study, it was found that there are several specific methodological principles carried out by Quraish Shihab and Hamka, including taking many sources of interpretation from other tafsirs and in their interpretation, it was found that both opinions were very thick with Indonesian culture.